Glucan main chain zwitterionic polyamino acid side chain brush polymer as well as preparation and application thereof
Through the hydration of the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer, the hydration layer is formed and the bacterial cell membrane is damaged, which solves the problem that the anti-adhesion coating cannot prevent bacterial growth and the toxicity of the bactericidal coating in the prior art. The problem has achieved efficient antibacterial and bactericidal effects and improved the prevention and treatment capabilities of medical devices.
Patent Information
- Application Number
- CN202411347830.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing anti-adhesive coating cannot prevent bacterial growth and biofilm formation. The bactericidal coating has problems with cytotoxicity and immune inflammatory response, making it difficult to effectively prevent and treat medical device-related infections.
The dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer is used to form a hydration layer through hydration to prevent bacteria from adhesion, and destroy bacterial cell membrane structure to achieve bactericidal function, and build a non-leaching, anti-adhesive and bactericidal dual-function type Antibacterial coating.
Effectively prevent bacterial initial adhesion and efficiently kill bacteria, significantly improve the antibacterial performance on the surface of medical devices, while avoiding cytotoxicity and immune inflammatory responses, and improving biosafety.
Smart Images

Figure CN119192591A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial coating materials, and in particular to a brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain and a preparation method and application thereof. Background Art
[0002] Bacterial infections caused by pathogenic bacteria seriously threaten human health and life, and bacterial infections have become one of the main causes of human death. Hospitals are the main place where bacterial infections occur and originate, and most of the nosocomial infections are caused by medical device-related infections. The adhesion, colonization, and reproduction of bacteria on the surface of medical devices, especially the surface of implantable / interventional medical instrument materials, can easily lead to the formation of bacterial biofilms on the surface of materials, which is the main cause of medical device-related infections. my country is a country with a large population and a serious aging population. Patients, mainly the elderly, often need to undergo various diagnostic and treatment measures during hospitalization and use a variety of medical instruments, such as endotracheal intubation, urinary catheter intubation, central venous cannulation, bone implant materials, etc. The surfaces of these materials provide a platform for bacterial adhesion and biofilm formation. Once formed, the biofilm on the surface of the material is difficult to remove and treat, causing continuous and repeated infections to patients, which not only increases the morbidity and mortality of patients, but also causes huge economic losses to patients and society. It can be seen that the prevention and treatment of medical device-related infections is of great urgency.
[0003] In response to the problem of medical device-related infection, researchers have developed coating materials with anti-bacterial adhesion function (referred to as anti-adhesion coating) and coating materials with bactericidal function (referred to as bactericidal coating). The anti-adhesion coating of the prior art can only inhibit the initial adhesion of bacteria on the surface of the material. Bacteria can often overcome the hydration of the coating surface to cause bacterial adhesion. This type of coating does not have a bactericidal function, and the bacteria will continue to proliferate and eventually lead to the formation of biofilms. In addition, the bactericidal coating cannot remove dead bacteria and their remains after killing the bacteria in contact with the surface. These substances cover the surface of the coating and shield the bactericidal function of the coating, causing the coating to reduce or completely lose its bactericidal activity. New pathogens are easy to adhere and proliferate on the surface of these substances, leading to the formation of biofilms. Dead bacteria and their remains adhered to the surface of the bactericidal coating are also prone to cause immune inflammatory responses in the human body. In addition, bactericidal coatings also have problems such as high cytotoxicity and poor biocompatibility.
[0004] Therefore, how to design a coating material that has both anti-bacterial adhesion and bactericidal functions without causing toxicity and immune inflammatory responses to human cells and tissues, thereby achieving the prevention and treatment of infections related to medical devices, especially implantable / interventional medical devices, has become one of the focuses of many forward-looking researchers in this field. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain and its preparation and application.
[0006] The brush-shaped polymer with a glucan main chain and zwitterionic polyamino acid side chains provided by the present invention can be used to prepare an antibacterial coating. When the antibacterial coating comes into contact with water molecules, the hydroxyl groups of the glucan and the zwitterionic groups of the polyamino acid are hydrated at the same time, and a hydration layer is formed on the surface of the coating to prevent the initial adhesion of bacteria and the nonspecific adsorption of proteins. When bacteria infect the surface of the material, the cationic groups of the polyamino acid can destroy the bacterial cell membrane structure, and the coating exhibits bactericidal activity.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] The first aspect of the present invention provides a brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain, wherein the structural formula of the brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain is as shown in formula (I):
[0009]
[0010] Here, x is an integer from 1 to 2000, y is an integer from 1 to 2000, and n is an integer from 1 to 1000.
[0011] x and y are the number of glucan units, n is the degree of polymerization of the polyamino acid, and the configuration of the polyamino acid is L-type, D-type or D / L-type.
[0012] The second aspect of the present invention provides a method for preparing a brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain, comprising the following steps:
[0013] (1) dissolving a monomer and cystamine dihydrochloride in a first solvent, and performing a ring-opening polymerization reaction to obtain a first polymer intermediate represented by formula (II); the monomer is γ-(3-methylthiopropyl)-L-glutamate-N-carboxylic acid anhydride and / or γ-(3-methylthiopropyl)-D-glutamate-N-carboxylic acid anhydride;
[0014] (2) dissolving the first polymer intermediate obtained in step (1) and tri(2-carboxyethyl)phosphine in a first solvent, and subjecting the resultant to a reduction reaction to obtain a second polymer intermediate represented by formula (III);
[0015] (3) dissolving dextran and maleic anhydride in a second solvent, and subjecting the mixture to an esterification reaction to obtain a third polymer intermediate represented by formula (IV);
[0016] (4) dissolving the second polymer intermediate obtained in step (2) and the third polymer intermediate obtained in step (3) in a second solvent, and subjecting them to Michael addition reaction to obtain a fourth polymer intermediate represented by formula (V);
[0017] (5) dissolving the fourth polymer intermediate obtained in step (4) and 2-bromoacetic acid in a third solvent, and performing an alkylation reaction to obtain a brush-shaped polymer having a glucan main chain and zwitterionic polyamino acid side chains as shown in formula (I);
[0018] The structural formulas of the above formula (I), formula (II), formula (III), formula (IV) and formula (V) are shown below:
[0019]
[0020]
[0021] Here, x is an integer from 1 to 2000, y is an integer from 1 to 2000, and n is an integer from 1 to 1000.
[0022] Furthermore, in step (1), the molar ratio of the monomer to cystamine dihydrochloride is (1-1000):1, preferably (1-100):1.
[0023] Furthermore, in step (1), the first solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, dichloromethane, chloroform and water.
[0024] Furthermore, in step (1), the temperature of the ring-opening polymerization reaction is 0 to 100°C.
[0025] Furthermore, in step (1), the ring-opening polymerization reaction time is 0.1 to 100 hours.
[0026] Furthermore, in step (1), after the ring-opening polymerization reaction, a precipitation step is also included.
[0027] Furthermore, in step (2), the molar ratio of the first polymer intermediate to tri(2-carboxyethyl)phosphine is 1:(1-100).
[0028] Furthermore, in step (2), the ratio of the mass of the first polymer intermediate to the volume of the first solvent is (1-200) mg:1 mL.
[0029] Furthermore, in step (2), the ratio of the mass of tri(2-carboxyethyl)phosphine to the volume of the first solvent is (1-200) mg:1 mL.
[0030] Furthermore, in step (2), the first solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, dichloromethane, chloroform and water.
[0031] Furthermore, in step (2), the temperature of the reduction reaction is 20 to 80°C.
[0032] Furthermore, in step (2), the reduction reaction time is 12 to 72 hours.
[0033] Furthermore, in step (3), the molar ratio of dextran to maleic anhydride is 1:(1-50).
[0034] Furthermore, in step (3), the ratio of the mass of the dextran to the volume of the second solvent is (1-200) mg:1 mL.
[0035] Furthermore, in step (3), the ratio of the mass of the maleic anhydride to the volume of the second solvent is (1-200) mg:1 mL.
[0036] Furthermore, in step (3), the second solvent is selected from one or more of dimethyl sulfoxide, triethylamine, N,N-dimethylformamide (DMF) and N,N-dimethylacetamide.
[0037] Furthermore, in step (3), the temperature of the esterification reaction is 20 to 80°C.
[0038] Furthermore, in step (3), the esterification reaction time is 12 to 72 hours.
[0039] Furthermore, in step (4), the molar ratio of the second polymer intermediate to the third polymer intermediate is (1-100):1.
[0040] Furthermore, in step (4), the ratio of the mass of the second polymer intermediate to the volume of the second solvent is (1-200) mg:1 mL.
[0041] Furthermore, in step (4), the ratio of the mass of the third polymer intermediate to the volume of the second solvent is (1-200) mg:1 mL.
[0042] Furthermore, in step (4), the second solvent is selected from one or more of dimethyl sulfoxide, triethylamine, N,N-dimethylformamide and N,N-dimethylacetamide.
[0043] Furthermore, in step (4), the temperature of the Michael addition reaction is 20 to 80°C.
[0044] Furthermore, in step (4), the Michael addition reaction time is 12 to 72 hours.
[0045] Furthermore, in step (5), the molar ratio of the fourth polymer intermediate to 2-bromoacetic acid is 1:(1-100).
[0046] Furthermore, in step (5), the ratio of the mass of the fourth polymer intermediate to the volume of the third solvent is (1-1000) mg:1 mL.
[0047] Furthermore, in step (5), the ratio of the mass of the 2-bromoacetic acid to the volume of the third solvent is (1-1000) mg:1 mL.
[0048] Furthermore, in step (5), the third solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and water.
[0049] Furthermore, in step (5), the temperature of the alkylation reaction is 30 to 100°C.
[0050] Furthermore, in step (5), the alkylation reaction time is 12 to 72 hours.
[0051] The present invention also protects the use of the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer described in the first aspect in the preparation of antibacterial coatings and medical devices.
[0052] The third aspect of the present invention provides an antibacterial coating comprising the brush-shaped polymer with a glucan backbone and zwitterionic polyamino acid side chains as described in the first aspect.
[0053] The antibacterial coating provided by the present invention has a three-dimensional network structure in which the molecules of the brush-shaped polymers of the glucan main chain zwitterionic polyamino acid side chains are cross-linked with each other and / or the molecules of the brush-shaped polymers of the glucan main chain zwitterionic polyamino acid side chains are cross-linked with each other.
[0054] Compared with the prior art, the present invention is aimed at the existing anti-adhesive coatings that have no bactericidal ability. Once bacteria adhere to the surface of the material, they cannot prevent the growth of bacteria and the formation of biofilms. Bactericidal coatings usually encounter problems such as dead bacteria adhesion, accumulation of bacterial debris, cytotoxicity, immune response or inflammation. The antibacterial coating provided by the present invention has anti-bacterial adhesion and bactericidal functions. When the antibacterial coating contacts water molecules, the hydroxyl groups of dextran and the zwitterionic groups of polyamino acids are hydrated at the same time. At this time, a hydration layer is formed on the surface of the coating to prevent the initial adhesion of bacteria and the nonspecific adsorption of proteins; when bacteria infect the surface of the material, the cationic groups of the polyamino acids can destroy the bacterial cell membrane structure, and the coating exhibits bactericidal activity.
[0055] Furthermore, the thickness of the antibacterial coating is 0.005-100 μm.
[0056] The fourth aspect of the present invention provides a method for preparing the antibacterial coating according to the third aspect, comprising the following steps:
[0057] S1. dissolving the glucan backbone zwitterionic polyamino acid side chain brush-shaped polymer and the cross-linking agent described in the first aspect of the present invention in a solvent, and performing a cross-linking reaction to obtain an antibacterial coating liquid;
[0058] S2. Apply the antibacterial coating liquid obtained in step S1 onto the substrate to obtain the antibacterial coating on the substrate.
[0059] Furthermore, in step S1, the concentration of the dextran main chain zwitterionic polyamino acid side chain brush polymer in the antibacterial coating liquid is 0.1-20wt%, and the concentration of the cross-linking agent in the antibacterial coating liquid is 0.1-20wt%.
[0060] Furthermore, in step S1, the cross-linking agent is selected from one or more of 2-(3,4-dihydroxyphenyl)ethylamine, D-3,4-dihydroxyphenylalanine, L-3,4-dihydroxyphenylalanine and L-3,4-dihydroxyphenylalanine hydrochloride.
[0061] Furthermore, in step S1, the solvent is selected from one or more of water, Tris buffer, ethanol, propanol, butanol, isopropanol, toluene, phthalates, ethyl acetate, dimethyl sulfoxide, tetrahydrofuran, acetone, cyclohexanone, butanone, n-heptane, heptane, cyclohexane, dichloromethane and chloroform.
[0062] Furthermore, in step S1, after dissolving the glucan main chain zwitterionic polyamino acid side chain brush polymer and the cross-linking agent described in the first aspect of the present invention in a solvent, the step of mixing for 0.1 to 2 hours is also included.
[0063] Furthermore, in step S1, the cross-linking reaction includes free radical reaction, oxidation reaction and Michael addition reaction.
[0064] Furthermore, in step S1, the temperature of the cross-linking reaction is 20-60°C.
[0065] Furthermore, in step S1, the cross-linking reaction time is 12 to 72 hours.
[0066] Furthermore, in step S2, the coating method includes dipping, brushing, and spraying.
[0067] Furthermore, in step S2, the material of the substrate is selected from one or more of polyethylene, polyvinyl chloride, polypropylene, polybutylene, polyurethane, polyimide, natural rubber, silicone, latex, thermoplastic elastomer, polytetrafluoroethylene, perfluoroethylene propylene copolymer, polystyrene, polycarbonate, polyetheretherketone and acrylonitrile-butadiene-styrene plastic.
[0068] A fifth aspect of the present invention provides a medical device comprising the antibacterial coating described in the third aspect.
[0069] Furthermore, the medical devices are mainly polymer medical devices, including medical catheters.
[0070] The present invention designs the coating based on the mechanism of initial bacterial adhesion and biofilm formation. Bacterial infection on the surface of medical devices often starts with the initial adhesion of bacteria, and then continues to grow and eventually evolves into bacterial biofilm infection, which requires the antibacterial coating material to have a prevention and control function corresponding to the bacterial infection process. In the initial bacterial adhesion stage, the antibacterial coating should have an anti-adhesion function and take into account biocompatibility. Once bacterial adhesion and infection occur, the antibacterial coating should have a bactericidal function to alleviate and treat bacterial infection. The brush-shaped polymer provided by the present invention has a hydrophilic main chain of polyhydroxyl groups and hydrophilic side chains of zwitterionic groups. Compared with anti-adhesive linear polymer coatings, the double hydration of the main chain and the side chain has higher antibacterial adhesion performance. Compared with bactericidal linear polymer coatings, the zwitterionic polymer side chains in the brush-shaped polymer can act synergistically to improve the bactericidal activity of the cationic groups in the polymer. At the same time, compared with medical devices that release bactericides to prevent and treat bacterial infections, this type of antibacterial method that fixes the coating on the surface of the material to prevent bacterial infection through contact sterilization can prevent the antibacterial agent from entering the human blood, tissue fluid, etc., avoid cell damage, and has higher biosafety.
[0071] Beneficial effects of the present invention:
[0072] The present invention provides a brush-shaped polymer with a glucan main chain and a zwitterionic polyamino acid side chain, which can be used to prepare an antibacterial coating. When the antibacterial coating contacts water molecules, the hydroxyl groups of the glucan and the zwitterionic groups of the polyamino acid are hydrated simultaneously, and a hydration layer is formed on the surface of the coating to prevent the initial adhesion of bacteria and the nonspecific adsorption of proteins. When bacteria infect the surface of the material, the cationic groups of the polyamino acid can destroy the bacterial cell membrane structure, and the coating exhibits bactericidal activity.
[0073] The present invention constructs a non-leaching, anti-adhesive and bactericidal dual-functional antibacterial coating based on a brush-shaped polymer on the surface of a polymer medical device through a cross-linking reaction. The preparation process is simple, the equipment requirements are low, the operation is easy, and the feasibility is high. The experimental results show that the surface treated with the coating provided by the present invention has better hydrophilicity and a significantly reduced water contact angle, which is attributed to the fact that the hydrophilic groups in the main chain and side chain of the brush-shaped polymer can bind to water, that is, double hydration. The antibacterial experimental results show that the surface of the brush-shaped polymer coating can effectively prevent the initial adhesion of bacteria and efficiently kill bacteria that contact the coating surface. The cytotoxicity experimental results show that the brush-shaped polymer coating is not toxic to mammalian cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 The synthetic route of brush-shaped polymers with zwitterionic polyamino acid side chains and dextran backbone.
[0075] Figure 2 For the first polymer intermediate 1 H NMR spectra.
[0076] Figure 3 For the second polymer intermediate 1 H NMR spectra.
[0077] Figure 4 1 and 2 are GPC diagrams of the first polymer intermediate and the second polymer intermediate.
[0078] Figure 5 For the fourth polymer intermediate 1 H NMR spectra.
[0079] Figure 6 It is a brush-shaped polymer with zwitterionic polyamino acid side chains and glucan backbone. 1 H NMR spectra.
[0080] Figure 7 This is a SEM image of the surface of the catheter with an antibacterial coating prepared in Example 1 after a bacterial adhesion test.
[0081] Figure 8 This is the SEM image of the catheter surface after the bacterial adhesion test without antibacterial coating modification.
[0082] Fig. 9 This is a data graph showing the number of colonies on a culture dish after the sterilization performance test of the catheter surface with an antibacterial coating prepared in Example 1 and the catheter surface without antibacterial coating modification.
[0083] Fig.10This is a statistical chart of the percentage of cell viability of the catheter surface with the antibacterial coating prepared in Example 1 and the catheter surface not modified with the antibacterial coating after being covered with mouse embryonic fibroblasts.
[0084] Fig.11 The figure is a statistical chart of the percentage of cell viability after covering human embryonic kidney cells on the surface of the catheter with antibacterial coating prepared in Example 1 and the surface of the catheter without antibacterial coating modification.
[0085] Fig.12 The graph shows the biofilm growth rate data of the catheter with antibacterial coating prepared in Example 1, the catheter with mixed cross-linked coating prepared in Comparative Example 1, the catheter with polydopamine coating prepared in Comparative Example 2, and the catheter not modified with antibacterial coating after being cultured in Staphylococcus aureus culture medium.
[0086] Fig.13 The data graph is a graph of biofilm growth rate after culturing the catheter with antibacterial coating prepared in Example 1, the catheter with mixed cross-linked coating prepared in Comparative Example 1, the catheter with polydopamine coating prepared in Comparative Example 2, and the catheter not modified with antibacterial coating in Escherichia coli culture medium.
[0087] Fig.14 This is a data graph showing the protein adsorption rate of the catheter with antibacterial coating prepared in Example 1, the catheter with polydopamine coating prepared in Comparative Example 2, the catheter with antibacterial coating prepared in Comparative Example 3, and the catheter not modified with antibacterial coating after incubation in fibrinogen solution.
[0088] Fig.15 CLSM images of the catheter with antibacterial coating prepared in Example 1, the catheter with antibacterial coating prepared in Comparative Example 3, and the catheter without antibacterial coating modification after being cultured in mouse mononuclear macrophage leukemia cells.
[0089] Fig.16 The data graph is a cell coverage data graph of the catheter with antibacterial coating prepared in Example 1, the catheter with antibacterial coating prepared in Comparative Example 3, and the catheter without antibacterial coating modification after being cultured in mouse mononuclear macrophage leukemia cells. DETAILED DESCRIPTION
[0090] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0091] The present invention provides a method for preparing a brush-shaped polymer with a zwitterionic polyamino acid side chain of a glucan main chain. The synthetic route is as follows: Figure 1 As shown, the following steps are included:
[0092] (1) The monomer and cystamine dihydrochloride are dissolved in a first solvent, and a first polymer intermediate (polyamino acid connected by disulfide bonds) is obtained after a ring-opening polymerization reaction. The hydrogen spectrum ( 1 H NMR) Figure 2 As shown;
[0093] (2) Dissolving the disulfide bonded polyamino acid and tri(2-carboxyethyl)phosphine in a first solvent and performing a reduction reaction to obtain a second polymer intermediate (polyamino acid with a thiol terminal group). The hydrogen spectrum ( 1 H NMR) Figure 3 As shown, the gel permeation chromatography (GPC) diagram of the first polymer intermediate and the second polymer intermediate is as shown Figure 4 As shown;
[0094] (3) dissolving dextran and maleic anhydride in a second solvent, and performing an esterification reaction to obtain a third polymer intermediate (maleic acid-modified dextran);
[0095] (4) The polyamino acid with a thiol terminal group and the maleic acid-modified dextran are dissolved in a second solvent, and subjected to Michael addition reaction to obtain a fourth polymer intermediate (polyamino acid-modified dextran). The hydrogen spectrum ( 1 HNMR) Figure 5 As shown;
[0096] (5) dissolving polyamino acid modified dextran and 2-bromoacetic acid in a third solvent, and performing an alkylation reaction to obtain the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer, and the hydrogen spectrum ( 1 H NMR) Figure 6 shown.
[0097] The present invention provides a method for preparing an antibacterial coating, comprising the following steps:
[0098] S1. The glucan main chain zwitterionic polyamino acid side chain brush-shaped polymer and the cross-linking agent provided by the present invention are dissolved in a solvent, and an antibacterial coating liquid is obtained after a cross-linking reaction;
[0099] S2. Apply the antibacterial coating liquid obtained in step S1 onto the substrate to obtain the antibacterial coating on the substrate.
[0100] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0101] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0102] Example 1
[0103] A method for preparing a urinary catheter with an antibacterial coating comprises the following steps:
[0104] S1. 120 mg of dextran main chain zwitterionic polyamino acid side chain brush polymer and 8 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 60 mL of Tris buffer, stirred at room temperature for 10 min, and an antibacterial coating liquid was obtained after cross-linking reaction;
[0105] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0106] In step S1, the brush-shaped polymer with zwitterionic polyamino acid side chains and glucan main chain is prepared by the following method:
[0107] (1) 3.1 g of γ-(3-methylthiopropyl)-L-glutamate-N-carboxylic acid anhydride and 140 mg of cystamine dihydrochloride were dissolved in 20 mL of N,N-dimethylformamide, and the mixture was subjected to a ring-opening polymerization reaction at room temperature for 24 h, and then precipitated with ether. The mixture was dried in vacuo to obtain a polyamino acid connected by a disulfide bond;
[0108] (2) 0.27 g of disulfide bond-linked polyamino acid and 30 mg of tri(2-carboxyethyl)phosphine were dissolved in 10 mL of N,N-dimethylformamide, and subjected to reduction reaction at room temperature for 24 h. After that, water was used for precipitation, and the polyamino acid with a thiol terminal group was obtained after vacuum drying;
[0109] (3) 0.5 g of dextran and 9 g of maleic anhydride were dissolved in 50 mL of DMF solvent, 36 μL of triethylamine was added, and the reaction was esterified at 60° C. for 24 h, and then precipitated with isopropanol. The reaction was dialyzed in a 3500 Da dialysis bag for 72 h, and then freeze-dried to obtain maleic acid-modified dextran;
[0110] (4) 0.21 g of polyamino acid with thiol terminal groups and 14 mg of maleic acid-modified dextran were dissolved in 3 mL of dimethyl sulfoxide, subjected to Michael addition reaction at room temperature for 24 h, and then precipitated with water. The polyamino acid-modified dextran was obtained after vacuum drying.
[0111] (5) 0.2 g of polyamino acid-modified dextran and 5 g of 2-bromoacetic acid were dissolved in N,N-dimethylformamide, and the mixture was subjected to alkylation reaction at room temperature for 48 h, and then dialyzed in a 50,000 Da dialysis bag for 72 h. After freeze-drying, the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer was obtained.
[0112] Example 2
[0113] A method for preparing a urinary catheter with an antibacterial coating comprises the following steps:
[0114] S1. 120 mg of dextran main chain zwitterionic polyamino acid side chain brush polymer and 8 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 60 mL of Tris buffer, stirred at room temperature for 10 min, and an antibacterial coating liquid was obtained after cross-linking reaction;
[0115] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0116] In step S1, the brush-shaped polymer with zwitterionic polyamino acid side chains and glucan main chain is prepared by the following method:
[0117] (1) 3.1 g of γ-(3-methylthiopropyl)-L-glutamate-N-carboxylic acid anhydride and 70 mg of cystamine dihydrochloride were dissolved in 20 mL of N,N-dimethylformamide, and the mixture was subjected to a ring-opening polymerization reaction at room temperature for 24 h, and then precipitated with ether. The mixture was dried in vacuo to obtain a polyamino acid connected by a disulfide bond;
[0118] (2) 0.27 g of disulfide bond-linked polyamino acid and 30 mg of tri(2-carboxyethyl)phosphine were dissolved in 10 mL of N,N-dimethylformamide, and subjected to reduction reaction at room temperature for 24 h. After that, water was used for precipitation, and the polyamino acid with a thiol terminal group was obtained after vacuum drying;
[0119] (3) 0.5 g of dextran and 9 g of maleic anhydride were dissolved in 50 mL of DMF solvent, 36 μL of triethylamine was added, and the reaction was esterified at 60° C. for 24 h, and then precipitated with isopropanol. The reaction was dialyzed in a 3500 Da dialysis bag for 72 h, and then freeze-dried to obtain maleic acid-modified dextran;
[0120] (4) 0.21 g of polyamino acid with thiol terminal groups and 14 mg of maleic acid-modified dextran were dissolved in 3 mL of dimethyl sulfoxide, subjected to Michael addition reaction at room temperature for 24 h, and then precipitated with water. The polyamino acid-modified dextran was obtained after vacuum drying.
[0121] (5) 0.2 g of polyamino acid-modified dextran and 5 g of 2-bromoacetic acid were dissolved in N,N-dimethylformamide, and the mixture was subjected to alkylation reaction at room temperature for 48 h, and then dialyzed in a 50,000 Da dialysis bag for 72 h. After freeze-drying, the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer was obtained.
[0122] Example 3
[0123] A method for preparing a urinary catheter with an antibacterial coating comprises the following steps:
[0124] S1. 120 mg of dextran main chain zwitterionic polyamino acid side chain brush polymer and 8 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 60 mL of Tris buffer, stirred at room temperature for 10 min, and an antibacterial coating liquid was obtained after cross-linking reaction;
[0125] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0126] In step S1, the brush-shaped polymer with zwitterionic polyamino acid side chains and glucan main chain is prepared by the following method:
[0127] (1) 3.1 g of γ-(3-methylthiopropyl)-L-glutamate-N-carboxylic acid anhydride and 140 mg of cystamine dihydrochloride were dissolved in 20 mL of N,N-dimethylformamide, and the mixture was subjected to a ring-opening polymerization reaction at room temperature for 24 h, and then precipitated with ether. The mixture was dried in vacuo to obtain a polyamino acid connected by a disulfide bond;
[0128] (2) 0.27 g of disulfide bond-linked polyamino acid and 30 mg of tri(2-carboxyethyl)phosphine were dissolved in 10 mL of N,N-dimethylformamide, and subjected to reduction reaction at room temperature for 24 h. After that, water was used for precipitation, and the polyamino acid with a thiol terminal group was obtained after vacuum drying;
[0129] (3) 0.5 g of dextran and 5 g of maleic anhydride were dissolved in 50 mL of DMF solvent, 36 μL of triethylamine was added, and the reaction was esterified at 60° C. for 24 h, and then precipitated with isopropanol. The reaction was dialyzed in a 3500 Da dialysis bag for 72 h, and then freeze-dried to obtain maleic acid-modified dextran;
[0130] (4) 0.21 g of polyamino acid with thiol terminal groups and 14 mg of maleic acid-modified dextran were dissolved in 3 mL of dimethyl sulfoxide, subjected to Michael addition reaction at room temperature for 24 h, and then precipitated with water. The polyamino acid-modified dextran was obtained after vacuum drying.
[0131] (5) 0.2 g of polyamino acid-modified dextran and 5 g of 2-bromoacetic acid were dissolved in N,N-dimethylformamide, and the mixture was subjected to alkylation reaction at room temperature for 48 h, and then dialyzed in a 50,000 Da dialysis bag for 72 h. After freeze-drying, the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer was obtained.
[0132] Example 4
[0133] A method for preparing a urinary catheter with an antibacterial coating comprises the following steps:
[0134] S1. 120 mg of dextran main chain zwitterionic polyamino acid side chain brush polymer and 8 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 60 mL of Tris buffer, stirred at room temperature for 10 min, and an antibacterial coating liquid was obtained after cross-linking reaction;
[0135] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0136] In step S1, the brush-shaped polymer with zwitterionic polyamino acid side chains and glucan main chain is prepared by the following method:
[0137] (1) 3.1 g of γ-(3-methylthiopropyl)-D-glutamate-N-carboxylic acid anhydride and 140 mg of cystamine dihydrochloride were dissolved in 20 mL of N,N-dimethylformamide, and the mixture was subjected to a ring-opening polymerization reaction at room temperature for 24 h, and then precipitated with ether. The mixture was dried in vacuo to obtain a polyamino acid connected by a disulfide bond;
[0138] (2) 0.27 g of disulfide bond-linked polyamino acid and 30 mg of tri(2-carboxyethyl)phosphine were dissolved in 10 mL of N,N-dimethylformamide, and subjected to reduction reaction at room temperature for 24 h. After that, water was used for precipitation, and the polyamino acid with a thiol terminal group was obtained after vacuum drying;
[0139] (3) 0.5 g of dextran and 9 g of maleic anhydride were dissolved in 50 mL of DMF solvent, 36 μL of triethylamine was added, and the reaction was esterified at 60° C. for 24 h, and then precipitated with isopropanol. The reaction was dialyzed in a 3500 Da dialysis bag for 72 h, and then freeze-dried to obtain maleic acid-modified dextran;
[0140] (4) 0.21 g of polyamino acid with thiol terminal groups and 14 mg of maleic acid-modified dextran were dissolved in 3 mL of dimethyl sulfoxide, subjected to Michael addition reaction at room temperature for 24 h, and then precipitated with water. The polyamino acid-modified dextran was obtained after vacuum drying.
[0141] (5) 0.2 g of polyamino acid-modified dextran and 5 g of 2-bromoacetic acid were dissolved in N,N-dimethylformamide, and the mixture was subjected to alkylation reaction at room temperature for 48 h, and then dialyzed in a 50,000 Da dialysis bag for 72 h. After freeze-drying, the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer was obtained.
[0142] Example 5
[0143] A method for preparing a urinary catheter with an antibacterial coating comprises the following steps:
[0144] S1. 120 mg of dextran main chain zwitterionic polyamino acid side chain brush polymer and 8 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 60 mL of Tris buffer, stirred at room temperature for 10 min, and an antibacterial coating liquid was obtained after cross-linking reaction;
[0145] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0146] In step S1, the brush-shaped polymer with zwitterionic polyamino acid side chains and glucan main chain is prepared by the following method:
[0147] (1) 3.1 g of γ-(3-methylthiopropyl)-L-glutamate-N-carboxylic acid anhydride and 140 mg of cystamine dihydrochloride were dissolved in 20 mL of N,N-dimethylformamide, and the mixture was subjected to a ring-opening polymerization reaction at room temperature for 24 h, and then precipitated with ether. The mixture was dried in vacuo to obtain a polyamino acid connected by a disulfide bond;
[0148] (2) 0.27 g of disulfide bond-linked polyamino acid and 30 mg of tri(2-carboxyethyl)phosphine were dissolved in 10 mL of N,N-dimethylformamide, and subjected to reduction reaction at room temperature for 24 h. After that, water was used for precipitation, and the polyamino acid with a thiol terminal group was obtained after vacuum drying;
[0149] (3) 0.5 g of dextran and 9 g of maleic anhydride were dissolved in 50 mL of DMF solvent, 36 μL of triethylamine was added, and the reaction was esterified at 60° C. for 24 h, and then precipitated with isopropanol. The reaction was dialyzed in a 3500 Da dialysis bag for 72 h, and then freeze-dried to obtain maleic acid-modified dextran;
[0150] (4) 0.21 g of polyamino acid with thiol terminal groups and 14 mg of maleic acid-modified dextran were dissolved in 3 mL of dimethyl sulfoxide, subjected to Michael addition reaction at room temperature for 24 h, and then precipitated with water. The polyamino acid-modified dextran was obtained after vacuum drying.
[0151] (5) 0.2 g of polyamino acid-modified dextran and 5 g of 2-bromoacetic acid were dissolved in N,N-dimethylformamide, and the mixture was subjected to alkylation reaction at room temperature for 48 h, and then dialyzed in a 50,000 Da dialysis bag for 72 h. After freeze-drying, the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer was obtained.
[0152] Comparative Example 1
[0153] A method for preparing a urinary catheter having a mixed cross-linked coating comprises the following steps:
[0154] S1. 60 mg of maleic acid-modified dextran, 60 mg of linear zwitterionic polyamino acid and 8 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 60 mL of Tris buffer, stirred at room temperature for 10 min, and subjected to cross-linking reaction to obtain an antibacterial coating liquid; the structural formula of the linear zwitterionic polyamino acid is as follows:
[0155]
[0156] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0157] Comparative Example 2
[0158] A method for preparing a urinary catheter having a polydopamine coating comprises the following steps:
[0159] S1. 60 mg of 2-(3,4-dihydroxyphenyl)ethylamine was dissolved in 30 mL of Tris buffer, stirred at room temperature for 10 min, and an antibacterial coating liquid was obtained after cross-linking reaction;
[0160] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0161] Comparative Example 3
[0162] A method for preparing a urinary catheter having an antimicrobial coating (a brush-shaped polymer coating based on mixed-charge polyamino acids) comprises the following steps:
[0163] S1. 60 mg of dextran main chain poly (lysine-random-glutamic acid) side chain brush-shaped polymer and 4 mg of 2-(3,4-dihydroxyphenyl)ethylamine were dissolved in 30 mL of Tris buffer, stirred at room temperature for 10 min, and cross-linked to obtain an antibacterial coating liquid; the structural formula of the dextran main chain poly (lysine-random-glutamic acid) side chain brush-shaped polymer is as follows:
[0164]
[0165] S2. Immerse the silicone catheter in the antibacterial coating solution obtained in step S1 for 24 hours, then take it out, repeatedly rinse the surface of the material with deionized water, and dry it at room temperature to obtain a catheter with an antibacterial coating.
[0166] Test Example 1
[0167] The change of water contact angle on the surface of the catheter before and after the modification of the antibacterial coating was tested. The test method was:
[0168] The contact angle of water droplets on the surface of the catheters with antibacterial coatings prepared in Examples 1 to 5 and the catheters without antibacterial coatings were tested using a water contact angle meter. Three points with a spacing of 5 mm were taken for each sample, and a total of 6 readings were taken to take the arithmetic average.
[0169] The test results are shown in Table 1:
[0170] Table 1
[0171] Contact angle before antibacterial coating modification (°) Contact angle after antibacterial coating modification (°) Example 1 101.2 21.5 Example 2 100.1 22.3 Example 3 103.2 26.3 Example 4 101.1 27.8 Example 5 101.2 23.2
[0172] As can be seen from Table 1, the water contact angle of the catheter surface modified with the antibacterial coating is significantly smaller than that of the unmodified catheter surface, indicating that the antibacterial coating significantly enhances the hydrophilicity of the device surface.
[0173] Test Example 2
[0174] The bacterial adhesion test was performed on the surface of the urinary catheter with the antibacterial coating prepared in Example 1 and the surface of the urinary catheter without the antibacterial coating modification.
[0175] The test method is as follows: the urinary catheter with antibacterial coating prepared in Example 1 and the urinary catheter without antibacterial coating are immersed in a solution with a concentration of 1×10 8 The specimens were placed in a bacterial culture solution and taken out after 48 h. They were immersed in a 2.5% glutaraldehyde aqueous solution at 4 °C overnight and then dehydrated using gradient ethanol. Finally, a scanning electron microscope (SEM) was used to observe the bacterial adhesion on the surface of the equipment.
[0176] Test results such as Figure 7 and Figure 8 As shown, Figure 7 This is a SEM image of the surface of the urinary catheter with an antibacterial coating prepared in Example 1 after a bacterial adhesion test. Figure 8 This is a SEM image of the catheter surface without antibacterial coating after the bacterial adhesion test. From the SEM image, it can be seen that there is basically no bacterial adhesion on the catheter surface with antibacterial coating, while there is a large amount of bacterial adhesion on the catheter surface without antibacterial coating modification.
[0177] Test Example 3
[0178] The bactericidal performance test was conducted on the surface of the urinary catheter with the antibacterial coating prepared in Example 1 and the surface of the urinary catheter without the antibacterial coating modification.
[0179] The test method is as follows: the urinary catheter with antibacterial coating prepared in Example 1 and the urinary catheter without antibacterial coating are immersed in a solution with a concentration of 1×10 6 The culture medium was added to 1% LB solid culture plate, and the plate was taken out after 24 hours. The bacteria adhering to the surface were washed with a sterile buffer solution and shaken for 0.5 hours. The bacterial suspension was diluted and plated on an LB solid culture plate. After culturing for 24 hours, the number of colonies on the culture plate was counted using a colony counter.
[0180] Test results such as Fig. 9 As shown, Fig. 9 The data graph of the number of colonies on the culture dish after the bactericidal performance test of the urinary catheter surface with antibacterial coating and the urinary catheter surface without antibacterial coating prepared in Example 1 is shown in FIG. Fig. 9 It can be seen that the surface of the catheter with antibacterial coating can effectively kill bacteria, while the surface of the catheter without antibacterial coating modification has no bactericidal performance.
[0181] Test Example 4
[0182] Cytotoxicity experiments were conducted on the surface of the catheter with antibacterial coating prepared in Example 1 and the surface of the catheter without antibacterial coating modification to verify the effect of the antibacterial coating modified instrument surface on the vitality of mammalian cells.
[0183] The test method is as follows: the surface of the catheter with antibacterial coating prepared in Example 1 and the surface of the catheter without antibacterial coating are lightly covered with mouse embryonic fibroblasts (NIH 3T3) and human embryonic kidney cells (HEK293T), respectively, with a cell concentration of 1×10 6 After 24 hours, the catheter was removed and the cell viability was analyzed and calculated using the MTT assay.
[0184] Test results such as Fig.10 and Fig.11 As shown, Fig.10 The figure is a statistical chart of the percentage of cell viability of the catheter surface with antibacterial coating prepared in Example 1 and the catheter surface without antibacterial coating after covering mouse embryonic fibroblasts, Fig.11 The figure is a statistical graph of the percentage of cell viability of the catheter surface with antibacterial coating prepared in Example 1 and the catheter surface without antibacterial coating after covering human embryonic kidney cells. It can be seen from the figure that the catheter surface with antibacterial coating prepared in Example 1 and the catheter surface without antibacterial coating modified have no obvious toxicity to mammalian cells.
[0185] Test Example 5
[0186] The performance of the catheter surface with an antibacterial coating prepared in Example 1, the catheter surface with a mixed cross-linked coating prepared in Comparative Example 1, the catheter surface with a polydopamine coating prepared in Comparative Example 2, and the catheter surface not modified with an antibacterial coating was tested for resistance to biofilm formation.
[0187] The test method is as follows: Staphylococcus aureus and Escherichia coli were cultured in LB broth at 37°C overnight. Then, the Staphylococcus aureus suspension was diluted to 1×10 8 CFU·mL -1 , dilute the E. coli suspension to the same concentration using M9 minimal medium.
[0188] The catheter with antibacterial coating prepared in Example 1, the catheter with mixed cross-linked coating prepared in Comparative Example 1, the catheter with polydopamine coating prepared in Comparative Example 2, and the catheter without antibacterial coating were immersed in a 1×10- 8 Three parallel samples were set up for each group of catheters in the bacterial culture medium and incubated at 37°C for 48 hours. During the incubation period, fresh culture medium was replaced every 24 hours. After 48 hours, the culture medium was carefully aspirated, the catheter was removed, and gently washed with PBS buffer to remove loose bacteria that had not yet formed a biofilm. The catheter was ultrasonically treated for 5 minutes to disperse the live bacteria into the PBS buffer. Subsequently, the bacterial suspension was continuously diluted to an appropriate concentration and spread on an agar plate. After 24 hours, the colony count was performed. The catheter without antibacterial coating modification was used as the control group, and the biofilm growth rate of the control group was 100% to calculate the growth rate of the biofilm on the catheter surface.
[0189] Test results such as Fig.12 and Fig.13 As shown, Fig.12 The data graph is a graph showing the biofilm growth rate of the urinary catheter with antibacterial coating prepared in Example 1, the urinary catheter with mixed cross-linked coating prepared in Comparative Example 1, the urinary catheter with polydopamine coating prepared in Comparative Example 2, and the urinary catheter without antibacterial coating modification after being cultured in Staphylococcus aureus culture solution. Fig.13The data graphs are of biofilm growth rate after culturing the catheter with antibacterial coating prepared in Example 1, the catheter with mixed cross-linked coating prepared in Comparative Example 1, the catheter with polydopamine coating prepared in Comparative Example 2, and the catheter without antibacterial coating modification in Escherichia coli culture medium. It can be seen from the graph that the surface of the catheter with antibacterial coating provided by the present invention can effectively inhibit the growth of biofilms of different bacteria, and has significantly improved antibacterial biofilm formation performance than the mixed cross-linked coating surface.
[0190] Test Example 6
[0191] The BCA method was used to determine the adsorption rate of protein on the surface of the catheter with an antibacterial coating prepared in Example 1, the surface of the catheter with a polydopamine coating prepared in Comparative Example 2, the surface of the catheter with an antibacterial coating prepared in Comparative Example 3, and the surface of the catheter that was not modified with an antibacterial coating.
[0192] The test method is: the catheter with antibacterial coating prepared in Example 1, the catheter with polydopamine coating prepared in Comparative Example 2, the catheter with antibacterial coating prepared in Comparative Example 3 and the catheter without antibacterial coating are immersed in a solution with a concentration of 2.5 mg·mL -1 % SDS solution and incubated at 37°C for 24 hours. Afterwards, the device surface was gently cleaned with deionized water. Next, the device was immersed in a 2wt.% SDS solution. Shake on an oscillator for 2 hours, followed by ultrasonic treatment in an ice water bath for 1 hour to ensure complete desorption of proteins adsorbed on the device surface. Afterwards, 100 μL of the protein solution was placed in a 96-well plate, and 100 μL of BCA reagent was added to each well. After the well plate was incubated at 60°C for 1 hour, the absorbance value was read at a wavelength of 560 nm using an enzyme-linked immunosorbent assay to determine the amount of protein adsorbed on the device surface. The catheter that was not modified with an antibacterial coating was used as the control group, and the protein adsorption rate of the control group was 100% to calculate the protein adsorption rate on the coating surface.
[0193] Test results such as Fig.14 As shown, Fig.14 The protein adsorption rate data of the urinary catheter with antibacterial coating prepared in Example 1, the urinary catheter with polydopamine coating prepared in Comparative Example 2, the urinary catheter with antibacterial coating prepared in Comparative Example 3 and the urinary catheter without antibacterial coating modification after incubation in fibrinogen solution are shown in FIG. Fig.14It can be seen that the catheter surface with an antibacterial coating (based on a brush-shaped polymer coating with zwitterionic polyamino acid side chains of a glucan backbone) prepared in Example 1 can effectively inhibit protein adsorption, and has significantly improved anti-protein adsorption performance compared with the catheter surface with an antibacterial coating (based on a brush-shaped polymer coating with mixed charge polyamino acids) prepared in Comparative Example 3.
[0194] Test Example 7
[0195] The anti-mammalian cell adhesion performance of the catheter surface with antibacterial coating prepared in Example 1, the catheter surface with antibacterial coating prepared in Comparative Example 3, and the catheter surface not modified with antibacterial coating was tested by confocal laser scanning microscopy (CLSM).
[0196] The test method is as follows: the catheter with antibacterial coating prepared in Example 1, the catheter with antibacterial coating prepared in Comparative Example 3 and the catheter without antibacterial coating modification are immersed in a newly cultured mouse mononuclear macrophage leukemia cell suspension (5×10 4 cells / well, 500 μL). Incubate in a cell culture incubator at 37°C for 24 hours to promote cell adhesion and growth. Next, replace fresh culture medium to ensure normal cell growth, and continue incubating in a cell culture incubator at 37°C for 24 hours. Then, remove the culture medium, take out the device, and gently wash the surface of the device with PBS buffer to remove loosely adhered cells. Subsequently, the cells adhered to the surface of the catheter were stained with Hoechest 33258 reagent for 20 minutes under light-proof conditions. After that, the surface of the device was gently washed, and the cells adhered to the surface of the catheter were fixed with a PBS solution containing 4wt.% paraformaldehyde. After 10 minutes, the device was gently washed with PBS buffer. The cells adhered to the surface of the catheter were observed by CLSM, and the cell coverage was calculated by Image J software.
[0197] Test results such as Fig.15 and Fig.16 As shown, Fig.15 The CLSM images of the urinary catheter with antibacterial coating prepared in Example 1, the urinary catheter with antibacterial coating prepared in Comparative Example 3 and the urinary catheter without antibacterial coating modification after being cultured in mouse mononuclear macrophage leukemia cells are shown in FIG. Fig.16The data graphs show the cell coverage of the catheter with antibacterial coating prepared in Example 1, the catheter with antibacterial coating prepared in Comparative Example 3, and the catheter without antibacterial coating modification after culture in mouse mononuclear macrophage leukemia cells. It can be seen from the graph that the surface of the catheter with antibacterial coating (based on brush-shaped polymer coating with zwitterionic polyamino acid side chains of glucan backbone) prepared in Example 1 can effectively inhibit the adhesion of mammalian cells on the surface of the device, and has significantly improved anti-cell adhesion performance than the surface of the catheter with antibacterial coating (based on brush-shaped polymer coating with mixed charge polyamino acid) prepared in Comparative Example 3.
[0198] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. It should be understood by those skilled in the art that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain, characterized in that: The structural formula of the dextran main chain zwitterionic polyamino acid side chain brush-shaped polymer is shown in formula (I): Here, x is an integer from 1 to 2000, y is an integer from 1 to 2000, and n is an integer from 1 to 1000.
2. A method for preparing a brush-shaped polymer with a glucan main chain zwitterionic polyamino acid side chain, characterized in that: The following steps are involved: (1) dissolving a monomer and cystamine dihydrochloride in a first solvent, and performing a ring-opening polymerization reaction to obtain a first polymer intermediate represented by formula (II); the monomer is γ-(3-methylthiopropyl)-L-glutamate-N-carboxylic acid anhydride and / or γ-(3-methylthiopropyl)-D-glutamate-N-carboxylic acid anhydride; (2) dissolving the first polymer intermediate obtained in step (1) and tri(2-carboxyethyl)phosphine in a first solvent, and subjecting the resultant to a reduction reaction to obtain a second polymer intermediate represented by formula (III); (3) dissolving dextran and maleic anhydride in a second solvent, and subjecting the mixture to an esterification reaction to obtain a third polymer intermediate represented by formula (IV); (4) dissolving the second polymer intermediate obtained in step (2) and the third polymer intermediate obtained in step (3) in a second solvent, and subjecting them to Michael addition reaction to obtain a fourth polymer intermediate represented by formula (V); (5) dissolving the fourth polymer intermediate obtained in step (4) and 2-bromoacetic acid in a third solvent, and performing an alkylation reaction to obtain a brush-shaped polymer having a glucan main chain and zwitterionic polyamino acid side chains as shown in formula (I); The structural formulas of the above formula (I), formula (II), formula (III), formula (IV) and formula (V) are shown below: Here, x is an integer from 1 to 2000, y is an integer from 1 to 2000, and n is an integer from 1 to 1000.
3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of the monomer to cystamine dihydrochloride is (1-1000):
1.
4. The preparation method according to claim 2, characterized in that: In step (3), the molar ratio of dextran to maleic anhydride is 1:(1-100).
5. The preparation method according to claim 2, characterized in that: In step (4), the molar ratio of the second polymer intermediate to the third polymer intermediate is (1-100):
1.
6. An antibacterial coating, characterized in that: The invention comprises the brush-shaped polymer having a glucan main chain and zwitterionic polyamino acid side chains as described in claim 1.
7. A method for preparing the antibacterial coating according to claim 6, characterized in that: The following steps are involved: S1. dissolving the glucan main chain zwitterionic polyamino acid side chain brush-shaped polymer and the cross-linking agent according to claim 1 in a solvent, and performing a cross-linking reaction to obtain an antibacterial coating liquid; S2. Apply the antibacterial coating liquid obtained in step S1 onto the substrate to obtain the antibacterial coating on the substrate.
8. The preparation method according to claim 7, characterized in that: In step S1, the concentration of the dextran main chain zwitterionic polyamino acid side chain brush polymer in the antibacterial coating liquid is 0.1-20wt%, and the concentration of the cross-linking agent in the antibacterial coating liquid is 0.1-20wt%.
9. The preparation method according to claim 7, characterized in that: In step S1, the cross-linking agent is selected from one or more of 2-(3,4-dihydroxyphenyl)ethylamine, D-3,4-dihydroxyphenylalanine, L-3,4-dihydroxyphenylalanine and L-3,4-dihydroxyphenylalanine hydrochloride.
10. A medical device, characterized in that: Comprising the antibacterial coating according to claim 6.
Citation Information
Patent Citations
Double-responsiveness glucan-polyamino acid block copolymer, preparation method of copolymer and drug-loaded micelle
CN104788670A
Preparation method of chitosan-g-antibacterial peptide polymer
CN108929387A
Biological macromolecule based on modified chitosan as well as preparation method and application thereof
CN109053928A
Hydrogel compositions based on polysaccharides and zwitterionic polymers, and methods for their use
US20210301108A1
High-permeability protein or polypeptide conjugate, and use thereof
WO2024159948A1